Spontaneous recanalization of extracranial internal carotid occlusion: A systematic scoping review - Sarah Y. Zhang; Hee Sahng Chung; Brian Dewar; Robert Fahed; Michel Shamy; Risa Shorr; Dar Dowlatshahi (PLoS ONE, 2025)
Introduction The spontaneous recanalization of an occluded extracranial internal carotid artery (ICA) is thought to be an uncommon etiology of ischemic stroke. However, a growing number of reports describe this phenomenon. We sought to perform a scoping review of the literature to assess the prevalence of spontaneous ICA recanalization and its timing in relation to occlusion, and any patterns in imaging and treatment. Methods MEDLINE, Embase, Cochrane Central Register of Controlled Trials and Web of Science were searched from inception to March 2024 for studies that included adults with spontaneous recanalization or transient occlusion of the extracranial internal carotid artery. Two investigators independently screened the studies and extracted data around recanalization proportion, timepoints, imaging, and treatment. These results were described qualitatively, and descriptive statistics were calculated where appropriate. Results Of 2807 studies screened, 53 met inclusion criteria, of which 17 were cohort studies and 36 were case studies, including a total of 818 patients. The proportion of recanalization was reported in 17 cohort studies for a median of 21.2% (IQR 9.2–37.5%). Amongst the studies which reported recanalization, 46.7% of those within the cohort studies recanalized within 6 months, whereas case studies reported that 66.7% of recanalizations occurred in that same timeframe. When reported, antiplatelet treatment was the most common medical treatment pre- and post-recanalization. Doppler imaging was used to identify recanalization in 67.9% of studies, and angiography was used in 54.7%. Twenty-one studies reported a revascularization procedure following spontaneous recanalization. Conclusions Spontaneous recanalization of an occluded extracranial carotid artery may occur, and possibly within 6 months after documented occlusion. However, clear data are lacking regarding a standard approach to imaging or treatment of patients with occluded carotid arteries.